2010
DOI: 10.1039/c0pp00105h
|View full text |Cite
|
Sign up to set email alerts
|

Design and introduction of a disulfide bridge in firefly luciferase: increase of thermostability and decrease of pH sensitivity

Abstract: The thermal sensitivity and pH-sensitive spectral properties of firefly luciferase have hampered its application in a variety of fields. It is proposed that the stability of a protein can be increased by introduction of disulfide bridge that decreases the configurational entropy of unfolding. A disulfide bridge is introduced into Photinus pyralis firefly luciferase to make two separate mutant enzymes with a single bridge. Even though the A103C/S121C mutant showed remarkable thermal stability, its specific acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 68 publications
0
35
0
1
Order By: Relevance
“…The design of proteins with enhanced thermostability is one of the major goals of protein engineering. Many attempts have been made by site directed mutagenesis to increase thermostability of firefly luciferase [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The design of proteins with enhanced thermostability is one of the major goals of protein engineering. Many attempts have been made by site directed mutagenesis to increase thermostability of firefly luciferase [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the thermal stability of the mutant A103C/S121C arises from the change of tertiary structure. Finally, these results showed that the engineered disulfide bridge not only did not destabilize the enzyme but also in one mutant it improved the specific activity and led to pH-insensitivity of the enzyme (Imani et al, 2010).…”
Section: Increase Of P Pyralis Luciferase Thermostability By Introdumentioning
confidence: 79%
“…On the other hand, introduction of disulfide bridges was found to be one of the most efficient strategies for increasing protein stability (Eijsink et al, 2004). Recently, disulfide bridges were introduced into P. pyralis firefly luciferase (Imani et al, 2010) by site-directed mutagenesis. Two different mutant proteins were made with a single bridge.…”
Section: Increase Of P Pyralis Luciferase Thermostability By Introdumentioning
confidence: 99%
“…However, as will be discussed later, recent experiments and theoretical calculation [67,68] demonstrated that the multicolor luminescence requires only the keto-form OxyLH 2 . Additionally, small alteration or lack of spectral shifts have been observed for firefly luciferase mutants and variants with many residue differences [69][70][71], which could not be explained by the mechanism proposed by White et al Meanwhile, the role of active site polarity in bioluminescence color has recently been considered as one of the most influent environmental factors in charge stabilization on phenolate ion of oxyluciferin. According to recent experimental observation and theoretical calculations, the light emitter of all color is the excited singlet state of the keto form of oxyluciferin phenolate anion [68].…”
Section: Enol-keto Tautomerization Of Oxyluciferinmentioning
confidence: 99%